Healthcare Facility Management in the United States (2008)
In the United States there is a close association between medical technology management (clinical engineering) and healthcare facility management (facility engineering). It is useful for clinical engineers to understand the work of facility engineers because both professions represent the application of engineering expertise to support safe and effective patient care. This article provides an overview of healthcare facility management practice in the United States.